2018
DOI: 10.1002/adbi.201800087
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Strength and the Supporting Material Strongly Influence the Adhesion of Silica to Supported Lipid Bilayers

Abstract: In the context of cell–nanoparticle interaction, the question arises how ions influence the adhesion between nanoparticles and cell membranes. Here, the question is addressed how the adhesion energy between supported lipid bilayers and silica particles helps to understand nanoparticle uptake. Supported lipid bilayers on mica and glass substrates serve as simple, well‐defined, and reproducible membrane models. Using atomic force microscopy with modified cantilevers, the interaction energy of both is found to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…However, adhesion energies ranging from 10 −5 to 1 mJ/m 2 are well-known under different conditions, 57,58 where adhesion can be measured without contact in the weak and ultraweak regimes. 59,60 A study of our group regarding the ion concentration switching on and off the adhesion energy was reported by Wittman et al 61 For a supported lipid bilayer in the fluid phase (DOPC) and a micrometer-sized silica bead, we found a saltdependent attraction threshold value, at about c crit = 15 mM NaCl. At higher salt concentrations, the adhesion energy saturates at about E adh = 60 μJ/m 2 , being significantly smaller than the one cited above.…”
Section: ■ Introductionsupporting
confidence: 61%
“…However, adhesion energies ranging from 10 −5 to 1 mJ/m 2 are well-known under different conditions, 57,58 where adhesion can be measured without contact in the weak and ultraweak regimes. 59,60 A study of our group regarding the ion concentration switching on and off the adhesion energy was reported by Wittman et al 61 For a supported lipid bilayer in the fluid phase (DOPC) and a micrometer-sized silica bead, we found a saltdependent attraction threshold value, at about c crit = 15 mM NaCl. At higher salt concentrations, the adhesion energy saturates at about E adh = 60 μJ/m 2 , being significantly smaller than the one cited above.…”
Section: ■ Introductionsupporting
confidence: 61%
“…A study of our group regarding the ion concentration switching on and off the adhesion energy, was reported by Wittman et al [54]. For a supported lipid bilayer in the fluid phase (DOPC) and a micrometer sized silica bead, we found a salt dependent attraction threshold value, at about ccrit = 15 mM NaCl.…”
Section: Introductionsupporting
confidence: 58%
“…Particle-size-dependent correlation between uptake rate and ionic concentration For the system studied in this work, a specific ionic environment is prerequisite in order to observe passive NP uptake. It has been shown that adhesion strength between silica particles and lipid membranes is strongly correlated to the ion concentration of the surrounding medium [14,34]. In the following section, we quantitatively determine the influence of salt concentration on the NP uptake.…”
Section: Resultsmentioning
confidence: 99%
“…For a deeper understanding of these effects, we here present additional data on uptake dynamics and dependencies on particle concentration and adhesion strength. In particular, we varied the adhesion strength and thus the driving force for NP uptake by adjusting the salt concentration for different particle sizes and concentrations [14]. In-depth experiments on these aspects will be followed by a discussion of a plausible theoretical picture of adhesion-driven particle uptake.…”
Section: Introductionmentioning
confidence: 99%